Medieval religious rationalities a weberian analysis - D'Avray, D. L. (Cambridge ; New York : Cambridge University Press, 2010)
"Inspired by the social theories of Max Weber, David d'Avray asks how far medieval religion was rational and, in doing so, proposes a new approach to the study of the medieval past. Applying ideas developed in his companion volume on Rationalities in History, he explores how values, instrumental calculation, legal formality and substantive rationality interact and the ways in which medieval beliefs were strengthened by their mutual connections, by experience, and by mental images. He sheds new light on key themes and figures in medieval religion ranging from conversion, miracles and the ideas of Bernard of Clairvaux to Trinitarianism, papal government and Francis of Assisi's charismatic authority. This book is unique in showing how values and instrumental calculation affect each other in practice and demonstrating the ways in which the application of social theory can be used to generate fresh empirical research as well as new historical insights"--Provided by publisher.
Preliminaries -- Medieval values : structures -- Medieval values : dynamics -- The value-instrumental interface in the Middle Ages -- Formal rationality and medieval religious law -- The formal-substantive interface and the dispensation system -- General conclusion.
Includes bibliographical references (p. 170-190) and indexes.
Description based on print version record.
Keywords: Church history -- Middle Ages, 600-1500.; Rationalism -- Philosophy; Values; Sociology; Weber, Max, -- 1864-1920.; Electronic books